Portable Child Seat Design for Motorcycle in the Front and Back Positions (Unijourn Publisher, 2021)
In Indonesia, it is a common practice for people in the urban area to bring children when riding a motorcycle. This habit raises a safety issue for the children as well as the motorcycle rider. For this reason, an additional child seat that allows the child to sit safely is demanded. This study aims to produce an innovative design of an additional child seat for a motorcycle that is portable, safe, durable, easy to use, and comfortable. The seat is designed so that it can be installed at the front and back sides of the rider in the motorcycle. The proposed model is designed to have a mass of between 0.6 to 3 kilograms. It is equipped with a seatbelt and head-protection pad. To evaluate the structural strength, theoretical analyses of solid mechanics were performed under static and fatigue loading conditions. As a result, the static safety factor of the child seat design for the front position was found to be 3.67. On the other hand, the fatigue safety factor of the child seat design for the front position was found to be 2.26, which is considered an infinite life. For the back position, the fatigue safety factor was found to be 2.36. The proposed design is expected to give a contribution to the development of innovative devices in transportation technology.